2014
DOI: 10.1103/physreve.90.022138
|View full text |Cite
|
Sign up to set email alerts
|

Jamming in finite systems: Stability, anisotropy, fluctuations, and scaling

Abstract: Athermal packings of soft repulsive spheres exhibit a sharp jamming transition in the thermodynamic limit. Upon further compression, various structural and mechanical properties display clean power-law behavior over many decades in pressure. As with any phase transition, the rounding of such behavior in finite systems close to the transition plays an important role in understanding the nature of the transition itself. The situation for jamming is surprisingly rich: the assumption that jammed packings are isotr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
128
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 39 publications
11
128
1
1
Order By: Relevance
“…By iteratively lowering σ t xy , we create configurations with σ xy spanning many orders of magnitude. This protocol is very similar to that used in isotropic jamming to obtain systems at target pressures [24,32,33]. Although some dependence on the packing fraction is expected, we find that it is weak for the system sizes studied.…”
Section: Mechanical Properties Of the Shear Jammed Statementioning
confidence: 72%
See 1 more Smart Citation
“…By iteratively lowering σ t xy , we create configurations with σ xy spanning many orders of magnitude. This protocol is very similar to that used in isotropic jamming to obtain systems at target pressures [24,32,33]. Although some dependence on the packing fraction is expected, we find that it is weak for the system sizes studied.…”
Section: Mechanical Properties Of the Shear Jammed Statementioning
confidence: 72%
“…In the thermodynamic limit, the bulk modulus jumps to a non-zero value while the shear modulus remains zero, so C αβγδ = Bδ αβ δ γδ . By spatial isotropy, the various shear moduli [33,34] in finite systems near jamming all scale the same way; the SO(3) rotational symmetry of isotropic jamming induces a symmetry in the various elastic moduli, all of which vanish linearly with ∆Z as ∆Z → 0 and N → ∞.…”
Section: Emergent Symmetry At the Shear Jamming Transitionmentioning
confidence: 99%
“…Note that B, G, and ΔZ should become independent of N in the large N limit, and it is well-established that ΔZ ∼ p 1=2 , B ∼ ΔZ 0 and G ∼ ΔZ in this regime (3,5,12). Furthermore, recent studies of finite-size effects found that NΔZ = FðNp 1=2 Þ (10, 12).…”
Section: Extracting Exponents and Numerical Verificationmentioning
confidence: 99%
“…The jamming transition marks the onset of rigidity in athermal sphere packings and was originally proposed as a zero-temperature transition (2,3) for soft repulsive spheres in a nonequilibrium "jamming phase diagram" (4) of varying packing density and applied shear. Many studies have documented behaviors characteristic of critical phenomena near the jamming transition, including power law scaling (2,3,5) and scaling collapses (6-13) of numerous properties, with the expression of quantities in terms of scaling functions, diverging length scales (6,(14)(15)(16)(17)(18)(19), and finite-size scaling (10,12,20). Theories have been developed to individually understand and relate some of these power laws (15,16,21,22), but a unified scaling theory has been lacking.…”
mentioning
confidence: 99%
“…Their findings caused the authors to question, if not the formal validity, then at least the use- fulness of linear elasticity in jammed solids -not just at the jamming point, but anywhere in the jammed phase. Subsequently, Van Deen et al [30] and Goodrich et al [31,32] argued that the situation is not so dire. They demonstrated that coarse grained properties of jammed solids are far less sensitive to contact changes than are the individual trajectories.…”
mentioning
confidence: 99%